School and neighbourhood segregation in Scotland and England - Elaine Drayton; Ellen Greaves; Gennaro Rossi (Institute for Fiscal Studies (IFS), 2023)
We document the patterns of neighbourhood and secondary school segregation across England and Scotland.
Keywords: 330; Education and skills; Education; Schools; Geography; Housing; Social mobility; Scotland